KARAKTERISTIK USAHA DAN PENDAPATAN NELAYAN DI SENDANG BIRU - Paulina Dua Mingga Nona Melci; Aldon Sinaga; Son Suwasono (BUANA SAINS, 2010)
More or less than 90% of fishery in Indonesia is dominated by small-scale fishery i.e. fishery used low technology and organized by small-scale capital. The other characteristics are the kind of rope is relatively simple and the number of fishes caught is usually low and various. This research which was located in Sitiarjo Village, Sumber Manjing Wetan District, Malang was determined intentionally by considering that the location is potential enough for fishery development. The number of sample taken was 25 people or 50% of population by simple random sampling method. The analysis method used were analysis of cost, revenue, income, and trading feasibility. The research result shows that in average the constant cost covers ships IDR 8,250,000; machines IDR 9,350,000; tools of piscotorial IDR 575,000; and iced boxes IDR 4,875,000; wereas the variable cost in average covers consumption IDR 46,148,400; fuel IDR 42,948,000; and block of ice IDR 33,360,198. All of cost was counted per year. The revenue in average is IDR 519,590,280; with income in average is IDR 374,095,682. The conclussion of this research is the trade characteristics of fishermen in research’s location uses the ship with type large net and boat, in average the number of ship used is 3 ships with machine capacity in average 158 machine capacity; whereas the tools of piscotorial used by the farmers are net and fishing-rod, with 12 ship-crews in average. The trading analysis shows that the trade of piscotorial in Sendang Biru is proper executed by score 3.57 R/C